Bioequivalence of Ertugliflozin/Sitagliptin Fixed‐Dose Combination Tablets and Coadministration of Respective Strengths of Individual Components. Issue 7 (20th June 2019) - Fediuk, Daryl J.; Matschke, Kyle; Liang, Yali; Pelletier, Kathleen B.; Wei, Hua; Shi, Haihong; Bass, Almasa; Hickman, Anne; Terra, Steven G.; Zhou, Susan; Krishna, Rajesh; Sahasrabudhe, Vaishali
Abstract: A fixed‐dose combination (FDC) tablet of ertugliflozin, a selective inhibitor of sodium‐glucose cotransporter 2, and sitagliptin, a dipeptidyl peptidase‐4 inhibitor, was developed for the treatment of patients with type 2 diabetes mellitus. Four studies were conducted under fasted conditions to demonstrate bioequivalence of ertugliflozin/sitagliptin FDC tablets and individual components at respective strengths when coadministered in healthy subjects. All studies had open‐label, randomized, 2‐period, 2‐sequence, single‐dose crossover designs. In each study 18 or 19 subjects were enrolled and received an ertugliflozin/sitagliptin FDC tablet (5 mg/50 mg, 5 mg/100 mg, 15 mg/50 mg, or 15 mg/100 mg) and corresponding strengths of ertugliflozin and sitagliptin coadministered as individual components. For both ertugliflozin and sitagliptin, the 90%CIs for the ratio (FDC:coadministration) of geometric means for area under the plasma concentration‐time profile from time 0 extrapolated to infinite time, and maximum observed plasma concentration, were within acceptance criteria for bioequivalence (80% to 125%). All adverse events were mild in intensity. The 4 studies demonstrated that each strength of FDC tablet is bioequivalent to the respective dose of coadministered individual components. This indicates that the known efficacy and tolerability of ertugliflozin and sitagliptin when coadministered can be translated to the use of a FDC formulation.